2019
DOI: 10.1021/acsami.9b17826
|View full text |Cite
|
Sign up to set email alerts
|

Biphasic Hydrogels Integrating Mineralized and Anisotropic Features for Interfacial Tissue Engineering

Abstract: The innate graded structural and compositional profile of musculoskeletal tissues interfaces is disrupted and replaced by fibrotic tissue in the context of disease and degeneration. Tissue engineering strategies focused on the restoration of the transitional complexity found in those junctions present special relevance for regenerative medicine. Herein, we developed a gelatinbased multiphasic hydrogel system where sections with distinct composition and microstructure were integrated in a single unit. In each p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 61 publications
2
46
0
Order By: Relevance
“…Anisotropic hydrogel scaffolds with oriented pores or channels provide guidance cues for cells, affecting their growth direction and rate. Studies have shown that anisotropic hydrogels were advantageous for PNI and SCI treatment because they promote glial cell and axonal alignment, outgrowth, and myelination [ [182] , [183] , [184] , [185] , [186] , [187] ]. De Laporte and co-workers defined the term Anisogel, where a soft hydrogel surrounded magneto-responsive short fibers that were directionally oriented [ 157 ].…”
Section: Anisotropic 3d Hydrogel Scaffoldsmentioning
confidence: 99%
“…Anisotropic hydrogel scaffolds with oriented pores or channels provide guidance cues for cells, affecting their growth direction and rate. Studies have shown that anisotropic hydrogels were advantageous for PNI and SCI treatment because they promote glial cell and axonal alignment, outgrowth, and myelination [ [182] , [183] , [184] , [185] , [186] , [187] ]. De Laporte and co-workers defined the term Anisogel, where a soft hydrogel surrounded magneto-responsive short fibers that were directionally oriented [ 157 ].…”
Section: Anisotropic 3d Hydrogel Scaffoldsmentioning
confidence: 99%
“…For example, diamagnetic nanoparticles, such as CNC, and superparamagnetic particles, such as CNC decorated with MNPs, have been used to produce anisotropy within natural and synthetic hydrogels [175,176]. For example, we developed an enzymatically crosslinked gelatin-based hydrogel system, showing sections with distinct composition and architecture integrated in a single unit in order to recreate the interfaces of the musculoskeletal system, such as the tendon-to-bone transition (also known as enthesis) [177]. On one hand, CNC loading in gelatin and exposure to a uniform magnetic field (400 mT) before crosslinking resulted in anisotropic structures that allowed hASCs alignment and the deposition of ECM proteins related to tendon.…”
Section: Anisotropic Hydrogelsmentioning
confidence: 99%
“…When the histograms did not fit to a Gaussian distribution (adjusted R-square < 0.8), we manually assigned values of FWHM = 180°, as previously described. [63,64] At least three images per condition were considered and a representative histogram for each condition was plotted.…”
Section: Nanocoating Of the Nanopatterned Surfaces With Platelet Lysatementioning
confidence: 99%